A New Hypothesis on the Origin of Water on Earth and Mars - Hans Merkl (Challenging Issues on Environment and Earth Science Vol. 3, 2021)
The question regarding the origin of water on Earth is still to be answered scientifically and accurately. It is certain that water in liquid or gaseous form could not have existed on the young, red-hot Earth. It is therefore generally assumed that comets brought water to Earth. However, the isotope ratio (H/D) of water on comets is more than double that of water on Earth, which means that only part of Earth´s water could have come from comets. Intensive laboratory experiments at the Tokyo Institute of Technology in Japan shows that, the stable bipolar magnetic field that we have today, that protects the Earth from the solar wind – a plasma flow of protons and electrons – was actually formed just less than one billion years ago. Interestingly, recent laboratory tests at the University of Maryland, USA, have shown that during the Earth´s early period, when its core of iron and nickel was still molten, the young Earth must have had a multipolar magnetic field. However, this multipolar magnetic field could not have provided any protection from the solar wind. In fact, it would have acted as a huge collector of the solar wind and the same would have applied to our neighboring planet Mars. The result from these two research experiments have now led to a completely new hypothesis regarding the origin of water on both Earth and Mars. During the early period of the two planets, the solar wind would have been able to penetrate along the vertical magnetic field lines into the dense, Venus-like carbon dioxide atmospheres of Earth and Mars. Because of the lack of an ozone layer, the atmosphere would have been exposed to the powerful ultraviolet rays and strong solar wind of the young Sun, which would have split the carbon dioxide molecules in the atmosphere into their component parts of oxygen and carbon. The oxygen released would therefore have been able to combine with the hydrogen nuclei of the solar wind to form water molecules which then fell down as rain.